Implementation of Total Ergonomics Approach through Multidisciplinary Sciences for the Improvement of Workers’ Health Quality: Literature Review Doctoral Dissertation Udayana Bali-Indonesia - Wahyu Susihono (Journal of Global Pharma Technology, 2017)
Total Ergonomics Approach is application of SHIP (Systemic, Holistic, Interdisciplinary and Participatory) through appropriate technology consideration in conducting design of working condition, work attitude and work system. The Total Ergonomics Approach model has been implemented in various disciplines such as Industrial, Agriculture, Fisheries, and Computer design, Education, Health, Hospitality, Building and Religious. Since 2006 to 2016 (10 years) was found nine scientific sectors that apply the concept of Total Ergonomics Approach. The results of the implementation indicate an incensement in the quality of workers’ health through the reduction of musculoskeletal complaints, fatigue, workload and some other complaints as an impact of ergonomic intervention. The science of ergonomics can be applied to solve various problems in a multidisciplinary range of sciences. Ergonomic improvements take account of human abilities, skills and limitations. Humans become the main factor in every design and improvement work.Keywords: Total Ergonomics, quality of work health, SHIP.